ROLE OF DIGITAL TECHNOLOGY ON BUSINESS EDUCATION STUDENTS’ ACADEMIC PERFORMANCE IN ABUBAKAR TAFAWA BALEWA UNIVERSITY (ATBU) BAUCHI (NAU Journal of Technology and Vocational Education, 2026)
The study focused on the Role of Digital Technology on Business Education Students’ Academic Performance in Abubakar Tafawa Balewa University (ATBU) Bauchi. In this study, two specific objectives and two research questions guided the conduct of the study. Relevant literature both conceptual and empirical are reviewed based on the study focus. The study used survey research design and that one hundred and four (104) 300L education students were used as population and 80 300L Business Education Students were used as a sample of the study. Structured questionnaire was used as an instrument for data collection. The instrument was validated by two experts. The data was collected by the researcher with the aid of two research assistants. Data collected were analyzed using descriptive statistics (i.e., mean and standard deviation). The findings of the study revealed a significant role of mobile phones and Artificial Intelligence (AI) on Business Education Students’ Academic Performance in Abubakar Tafawa Balewa University (ATBU) Bauchi. To the best of the researcher’s knowledge, little or no published study was found on Role of Digital Technology on Business Education Students’ Academic Performance in Abubakar Tafawa Balewa University (ATBU) Bauchi.
Keywords: Digital Technology; Academic Performance; Artificial Intelligence